2022
DOI: 10.1136/bcr-2021-248415
|View full text |Cite
|
Sign up to set email alerts
|

Non-arteritic anterior ischaemic optic neuropathy (NA-AION) and COVID-19 vaccination

Abstract: A woman in her 50s presented with diminution of vision in her left eye (OS) 4 days after COVISHIELDTM vaccination. She had been diagnosed with non-arteritic anterior ischaemic optic neuropathy (NA-AION) of right eye (OD) 8 months earlier. The present episode revealed a best-corrected visual acuity (BCVA) of 20/50 in OD and 20/20 in OS with grade 1 relative afferent pupillary defect. Fundus evaluation showed pale disc in OD and temporal disc oedema in OS. Humphrey’s visual field analysis showed incomplete infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…It has also been reported that after COVID-19 vaccination, platelets are activated, the coagulation system is markedly stimulated, and serious thromboembolic complications may be triggered [ 6 , 7 , 19 ], which may have been the cause of retinal artery occlusion in the first case. After COVID-19 vaccination, neutralising antibody levels reached a maximum at approximately two weeks and then declined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that after COVID-19 vaccination, platelets are activated, the coagulation system is markedly stimulated, and serious thromboembolic complications may be triggered [ 6 , 7 , 19 ], which may have been the cause of retinal artery occlusion in the first case. After COVID-19 vaccination, neutralising antibody levels reached a maximum at approximately two weeks and then declined.…”
Section: Discussionmentioning
confidence: 99%
“…AAION accounts for 5-10% of all anterior ischaemic optic neuropathies but is very rare in Japan [2,3]. Many vaccines have been approved worldwide to control the coronavirus disease-19 (COVID- 19) pandemic. In Japan, the Pfizer and Moderna vaccines are mainly used, and vaccination is recommended.…”
Section: Introductionmentioning
confidence: 99%
“…Optic neuropathy is suspected as one of adverse events of the COVID-19 vaccine, which includes ON associated with or without demyelinating CNS diseases [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], NA-AION [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], and NMOSD [ 8 , 9 ]. Lotan et al reviewed 14 case reports and 2 case series by electronic searches of the published literature regarding neuro-ophthalmological complications of COVID-19 vaccines and reported that optic neuritis was the most common, occurring in 61 of 76 cases (80.3%) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ocular adverse effects observed following administration of COVID-19 vaccines include episcleritis, scleritis, anterior uveitis, acute macular neuroretinopathy, paracentral acute middle maculopathy, central serous chorioretinopathy (CSCR), ophthalmic vein thrombosis, Vogt-Koyanagi-Harada disease (VKH), acute zonal occult outer retinopathy (AZOOR), multifocal choroiditis, arteritic anterior ischemic optic neuropathy (AAION), non- arteritic anterior ischemic optic neuropathy (NA-AION), Graves disease, cranial nerve palsies like facial or abducens nerve palsies, acute zoster ophthalmicus (HZO), acute retinal necrosis and multiple evanescent white dot syndrome(MEWDS). 10 , 11 , 12 , 13 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%